1986
DOI: 10.1099/0022-1317-67-7-1479
|View full text |Cite
|
Sign up to set email alerts
|

A Neutralizing Monoclonal Antibody to Respiratory Syncytial Virus which Binds to Both F1 and F2 Components of the Fusion Protein

Abstract: SUMMARYA virus-neutralizing monoclonal antibody (1E3) specifically immunoprecipitated the 70000 mol. wt. (70K) fusion (F) protein from respiratory syncytial (RS) virusinfected HeLa cells. Western blotting analysis of polypeptides from such cells separated by SDS-polyacrylamide gel electrophoresis (SDS-PAGE) under reducing conditions revealed that 1E3 was peculiar in that it bound to both F1 (50K) and F: (20K) components of the F protein. Antibody subsequently eluted from either the F1 or the F2 regions of immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

1987
1987
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 13 publications
1
22
1
Order By: Relevance
“…The two neutralizing, fusion-inhibiting MAbs chosen for mapping, 1E3 and RS348, have previously been shown to bind to the F protein in the presence of SDS and 2-mercaptoethanol indicating that at least some of their binding capacity is conformation-independent (Samson et al, 1986;Bourgeois et al, 1991). Both of these also bound to the C-terminal half of the molecule and to fragments containing amino acids 253 to 289 but not to fragments containing only sequences N-terminal to amino acid 212.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two neutralizing, fusion-inhibiting MAbs chosen for mapping, 1E3 and RS348, have previously been shown to bind to the F protein in the presence of SDS and 2-mercaptoethanol indicating that at least some of their binding capacity is conformation-independent (Samson et al, 1986;Bourgeois et al, 1991). Both of these also bound to the C-terminal half of the molecule and to fragments containing amino acids 253 to 289 but not to fragments containing only sequences N-terminal to amino acid 212.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse ascitic fluids containing MAbs IE3 and 348 to the RS virus F protein were described previously (Samson et al, 1986;Bourgeois et al, 1991). Ascites fluid containing MAb 1G9 to the capsid protein of feline calicivirus which served as a control for non-specific binding was described by Carter et al (1989).…”
Section: Methodsmentioning
confidence: 99%
“…The results were obtained at the 1/128 dilution of serum, which represented the last dilution at which complete neutralization was observed. Several distinct neutralization epitopes on the fusion protein have been reported (Samson et al, 1986;Walsh et al, 1986;Trudel et al, 1987). Walsh et al (1986), using 13 MAbs, have identified three neutralizing sites on the fusion protein.…”
Section: Resultsmentioning
confidence: 99%
“…This speckling, which had faded by 8 h p.i., was most obvious with anti-22K protein MAb but 0000-7621 © 1987 SGM Single cell suspensions were prepared using EDTA, fixed in acetone and stained by the indirect immunofluorescence technique (Scott et al, 1976;Gardner & McQuillin, 1980). Anti-RS virus MAbs (Table 1, , 1987Samson et al (1986). ~" Department of Virology, Karolinska Institute, State Bacteriological Laboratory, S-105 21 Stockholm, Sweden.…”
Section: Discussionmentioning
confidence: 99%